Burkholderia Cepacia in Patients with Diabetes Mellitus - An unusal Presentation - Bhat, Neeti; Karna, Alina; Dutta, Sameer (Nepal Journal of Health Sciences, 2021)
Burkholderia Cepacia is an aerobic gram-negative bacillus, rarely affects immunocompetent individuals, usually found in various aquatic environments. We present a case of a 45-year-old male with a known case of diabetes for five years. He presented with high-grade fever, dysuria, and abdominal pain. Routine tests, ultrasonography along together with high-resolution computed tomography was done. High Resolution Computed Tomography showed subtle ground-glass opacity of the superior segment of lingulae of the left lobe of the lungs. Real time polymerase chain reaction was advised to rule out Covid-19 infection, which was negative. Burkholderia Cepacia was identified in Cystine- Lactose-Electrolyte-Deficient Agar culture (CLED).